2015
DOI: 10.1186/s13059-015-0675-4
|View full text |Cite
|
Sign up to set email alerts
|

Extensive rewiring of epithelial-stromal co-expression networks in breast cancer

Abstract: BackgroundEpithelial-stromal crosstalk plays a critical role in invasive breast cancer pathogenesis; however, little is known on a systems level about how epithelial-stromal interactions evolve during carcinogenesis.ResultsWe develop a framework for building genome-wide epithelial-stromal co-expression networks composed of pairwise co-expression relationships between mRNA levels of genes expressed in the epithelium and stroma across a population of patients. We apply this method to laser capture micro-dissecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 93 publications
2
44
0
Order By: Relevance
“…This analysis revealed 18,849,925 significant (FDR Ͻ 0.05) epithelial-stromal coexpression interactions significant at FDR Ͻ 0.05 (Table 7). In comparison, Oh et al (41) reported 929 significant epithelial-stromal coexpression interactions among 11,700 ϫ 11,700 ϭ 136,890,000 pairwise associations tested in normal breast tissue. Interestingly, all the top detected genes have been implicated in the link between inflammation and cancer of the colon (5,18,20,35,39,44,46,49,56,62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis revealed 18,849,925 significant (FDR Ͻ 0.05) epithelial-stromal coexpression interactions significant at FDR Ͻ 0.05 (Table 7). In comparison, Oh et al (41) reported 929 significant epithelial-stromal coexpression interactions among 11,700 ϫ 11,700 ϭ 136,890,000 pairwise associations tested in normal breast tissue. Interestingly, all the top detected genes have been implicated in the link between inflammation and cancer of the colon (5,18,20,35,39,44,46,49,56,62).…”
Section: Discussionmentioning
confidence: 99%
“…In complementary analyses, the effect of tissue type and biopsy site location on gene expression was assessed. For this purpose, stromal-epithelial gene coexpression relationships were assessed using simple linear regression models, which provide a basis for comparison between our results and similar studies (41).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have underscored the important contribution of stromal gene expression and morphologic phenotypes to cancer growth and progression for breast cancer (2,3,47). The implication of tumor stroma to prognosis could be different for different cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Oh et al reported a systems level approach for epithelial stromal co-expression networks in breast cancer using earlier available transcriptomic data (69). This would have a significant impact on designing the drugs with high efficacy to treat cancer.…”
Section: Epithelial-stromal Interaction Networkmentioning
confidence: 99%